2020
DOI: 10.1111/1759-7714.13743
|View full text |Cite
|
Sign up to set email alerts
|

Tissue surface area and tumor cell count affect the success rate of the Oncomine Dx Target Test in the analysis of biopsy tissue samples

Abstract: Background: The Oncomine Dx Target Test (ODxTT) is a next-generation sequencing-based companion diagnostic test which has been recently developed; however, its analysis success rate could be improved, especially for small samples. The aim of this study was to identify the pathological factors associated with biopsy specimens that affect the analysis success rate of ODxTT. Methods: We retrospectively investigated 119 cases subjected to ODxTT at Kanagawa Cancer Center. Data pertaining to the results of BRAF V600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…In a previous work, we examined the correlation between the tumor surface area and the success rate of ODxTT, and reported that a tumor surface area ≥ 1 mm 2 was the best discriminative value to identify samples for ODxTT analyses [15]. In the present study, the success rate of NGS in samples with a tumor surface area ≥ 1 mm 2 was higher than that in samples with a tumor surface area < 1 mm 2 .…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…In a previous work, we examined the correlation between the tumor surface area and the success rate of ODxTT, and reported that a tumor surface area ≥ 1 mm 2 was the best discriminative value to identify samples for ODxTT analyses [15]. In the present study, the success rate of NGS in samples with a tumor surface area ≥ 1 mm 2 was higher than that in samples with a tumor surface area < 1 mm 2 .…”
Section: Discussionmentioning
confidence: 43%
“…However, in practice, a sufficient amount of tissue is required to allow successful analysis with NGS, including ODxTT. We previously reported a correlation between the tissue surface area of a biopsy specimen and the success rate of ODxTT in detecting the BRAF V600E mutation and showed that the optimal cut-off value for this tissue surface area is 1.04 mm 2 [15].…”
Section: Introductionmentioning
confidence: 99%
“…This may have led to subconscious bias, although the operators performed the EBUS-TBNA procedure with the best intentions in the same manner. Fourth, it was considered that large sample size and high number of malignant cells are associated with the high success rate of NGS (25), in that point, we thought 22G needle was more suitable for NGS than 25G needle. But we did not directly compare the success rate of molecular test including NGS between the 22G and 25G needle.…”
Section: Discussionmentioning
confidence: 97%
“…These studies have shown that the presence of a larger number of malignant cells was associated with higher success rates of NGS. Furthermore, in a study that evaluated the sample size, number of malignant cells in biopsy samples of lung cancer and the success rate of NGS, larger sample sizes and higher numbers of malignant cells in the samples were associated with higher success rates of NGS (25). Thus, our finding that TBNA using the 22G needle yielded larger sizes of tissue samples without a decrease in the percentage of malignant cells and samples containing a higher proportion of malignant cells may indicate that TBNA performed with the 22G needle may also be associated with an improved success rate of biomarker analysis in patients with advanced NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…However, in practice, a sufficient amount of tissue is required to allow successful analysis with NGS, including ODxTT. We previously reported a correlation between the tissue surface area of a biopsy specimen and the success rate of ODxTT in detecting the BRAF V600E mutation, and showed that the optimal cut-off value for this tissue surface area is 1.04 mm 2 [15]. Transbronchial biopsy (TBB) with endobronchial ultrasonography with a guide sheath (EBUS-GS) is generally recognized as a useful method for the diagnosis of suspected lung-cancer lesions.…”
Section: Introductionmentioning
confidence: 99%